Implementasi metode Ward clustering untuk klasterisasi penduduk yang memiliki jaminan kesehatan pada kabupaten dan kota di Provinsi Maluku - Matdoan, Muhammad Yahya; Balami, Abdul Malik; Talakua, Mozart Winston (Jurusan Matematika FMIPA Universitas Jember, 2023)
The Health Insurance Program is a protection guarantee for comprehensive health services which includes promotive, preventive and curative and rehabilitative services provided in stages for the community/participants whose contributions are paid by the government. The health insurance program in Maluku Province from year to year has been getting better. However, there are still disparities or gaps between regions in Maluku Province, so it is necessary to study the clusterization of the population who have health insurance in districts/cities in Maluku Province. Ward clustering method is a method that aims to get a cluster that has the smallest possible internal cluster variance. The purpose of this study is to obtain a cluster of residents who have health insurance in districts/cities in Maluku Province. The data used in this study were sourced from Maluku publications in figures at the Maluku Province BPS. This study obtained the results that there are 3 clusters in the cluster of residents who have health insurance in districts/cities in Maluku Province with details of cluster 1 consisting of Tanimbar Islands Regency, Central Maluku, Buru, West Seram, East Seram and South Buru District. Cluster 2 consists of Southeast Maluku Regency, Aru Islands, Southwest Maluku and Tual City. Furthermore, Cluster 3 consists of Ambon City. Keywords: Clustering, health insurance, wardMSC2020: 62H30